Early identification of unusually clustered mutations and root causes in therapeutic antibody development. Issue 9 (6th June 2018) - Qian, Yueming; Chen, Zhiqiang; Huang, Xin; Wang, Xuning; Xu, Xuankuo; Kirov, Stefan; Ludwig, Richard; Qian, Nan‐Xin; Ravi, Kandasamy; Tao, Li; Borys, Michael C.; Li, Zheng Jian
Abstract: This study reports findings of an unusual cluster of mutations spanning 22 bp (base pairs) in a monoclonal antibody expression vector. It was identified by two orthogonal methods: mass spectrometry on expressed protein and next‐generation sequencing (NGS) on the plasmid DNA. While the initial NGS analysis confirmed the designed sequence modification, intact mass analysis detected an additional mass of the antibody molecule expressed in CHO cells. The extra mass was eventually found to be associated with unmatched nucleotides in a distal region by checking full‐length sequence alignment plots. Interestingly, the complementary sequence of the mutated sequence was a reverse sequence of the original sequence and flanked by two 10‐bp reverse‐complementary sequences, leading to an undesirable DNA recombination. The finding highlights the necessity of rigorous examination of expression vector design and early monitoring of molecule integrity at both DNA and protein levels to prevent clones from having sequence variants during cell line development. Abstract : This study reports findings of an unusual cluster of mutations spanning 22 base pairs in a monoclonal antibody expression vector. It was identified by two orthogonal methods: mass spectrometry on expressed protein and next‐generation sequencing on the plasmid DNA.